COVID-19 presenting with diarrhoea and hyponatraemia. Issue 6 (7th June 2020) - Ata, Fateen; Almasri, Hussam; Sajid, Jamal; Yousaf, Zohaib
Abstract : COVID-19 is a viral disease with a high infectivity rate. The full spectrum of the disease is not yet understood. This understanding may help in limiting potential exposure. We present a young man with diarrhoea, abdominal pain and hyponatraemia who turned out to be positive for COVID-19.